Spermine-mediated polyamine metabolism enhances arsenic-stress tolerance in Phaseolus vulgaris by expression of zinc-finger proteins related genes and modulation of mineral nutrient homeostasis and antioxidative system. (1st May 2022) - Shah, Anis Ali; Riaz, Luqman; Siddiqui, Manzer H.; Nazar, Rabia; Ahmed, Shakil; Yasin, Nasim Ahmad; Ali, Aamir; Mukherjee, Soumya; Hussaan, Muhammad; Javad, Sumera; Chaudhry, Ozair
Abstract: The contamination of groundwater and agricultural land by metalloids especially arsenic (As) is one of the most serious threats to people and plants worldwide. Therefore, the present study was design to explore the role of spermine (Spm)- mediated polyamine metabolism in the alleviation of arsenic (As) toxicity in common bean ( Phaseolus vulgaris L.). It was noted that As stress caused reduction in the intracellular CO2 concentration, stomatal conductivity and transpiration rate as compared to the control treatment and also impairedplant growth attributes and mineral nutrient homeostasis (sulfur, phosphorus, potassium and calcium). However, the exogenous application of Spm resulted in a considerable enhance in the content of glutathione and nitric oxide, and the activity of superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), glutathione-reductase (GR), ascorbate peroxidase (APX), monodehydroascorbate reductase (MDHAR) in P. vulgaris seedlings grown As-contaminated soil. In addition, Spm application significantly improved the endogenous production of putrescine and spermidine accompanied along with reduction in malondialdehyde, electrolyte leakage, hydrogen peroxide, superoxide level besides enhanced methylglyoxal (MG) detoxification. Moreover, Spm treatment elevated the expression level of zinc-finger proteins related genes ( PvC3H24, PvC3H25, PvC3H26 and PvC3H27 ) involved in abiotic stress response. The study concluded that Spm acted as an enhancing agent and improved tolerance to As-toxicity by upregulating the expression of zinc-finger proteins related genes, polyamine metabolism, Mg detoxification and antioxidant system in P. vulgaris . Highlights: Arsenic (As) stress reduced growth and physiochemical features of P. vulgaris . Spm application enhanced morpho-physiological characteristics in P. vulgaris . As stress tolerance was ascribed to enhanced activity of antioxidant enzymes. Spm regulated zinc-finger proteins related genes and mineral nutrient homeostasis.